Association between poor self-reported health and unmarried status among adults: examining the hypothesis of marriage protection and marriage selection in the Indian context - Hossain, Babul; James, K. S. (BMC public health, 2022)
Background The link between marital status and health differences has long been a topic of debate. The substantial research on marriage and health has been conducted under two important hypotheses: marital protection and marriage selection. While the majority of evidence on the marriage-health relationship using these hypotheses comes from developed countries, there is a lack of evidence from Asia, particularly from India. Objectives The current study examines theoretical frameworks of marriage i.e., marital protection and marriage selection in the Indian setting concurrently, bringing substantial empirical evidence to explore the link between marriage and health, considering this subject in the context of self-reported health (SRH). Secondly, this study will aid in investigating age and gender differences in marriage and health. Methods Using the Study on Global AGEing and Adult Health (SAGE), a cohort study of individuals aged 50 years and older with a small section of individuals aged 18 to 49 for comparative reasons, the present study population was 25 years and above individuals with complete marital information. Logistic regressions were employed to explore the connection between marital status and self-reported health. In the marriage protection hypothesis, the follow-up poor SRH was the dependent variable, whereas the initial unmarried status was the independent variable. For the marriage selection effects, initial poor SRH as the independent variable and follow-up unmarried status as the dependent variable had considered. Results Examining the marital protection hypothesis, the initial unmarried status (OR: 2.14; CI at 95%: 1.17, 3.92) was associated with the followed-up SRH transition from good to poor between 2007 and 2015 for young men, while initial unmarried status was linked with a lower likelihood of stable good SRH and a higher likelihood of stable poor SRH status across all age categories among women. Focusing on the marriage selection hypothesis, among young men, a significant association exists between the initial poor SRH and departure in marital status from married to unmarried. Young women with initial poor SRH (OR: 0.68; CI at 95%: 0.40, 1.00) had lower odds of stable married. In comparison, women with initially poor SRH, irrespective of age, were more likely to have higher odds of being stably unmarried. Conclusion Marriage indeed protects health. There are also shreds of evidence on health-selected marital status in India. Taken together, the aspect of marital protection or marriage selection is gender and age-specific in India. The findings contribute to a more comprehensive understanding of the relationship between marriage and health, which may have significant implications for health-related public policies aimed at unmarried women. Keywords: Marriage protection, Marriage selection, Unmarried women, SAGE, India